Enhancing coiled solar still performance with vertical wick distiller, reflectors, nanomaterial-infused PCM, and condenser integration - Mamdouh I. Elamy; Suha A. Mohammed; Ali Basem; Wissam H. Alawee; A.S. Abdullah; A. Aldabesh; Hasan Sh Majdi; Z.M. Omara; Fadl A. Essa (Case Studies in Thermal Engineering, 2024)
This study explored methods to enhance the performance of a coiled solar still (COSS). One technique involved adding a vertical wick distiller (VWSS) with built-in reflectors positioned after the COSS. Additionally, the research examined the impact of incorporating a fan and a separate condenser on the COSS's distillate output. Finally, the investigation assessed the potential advantages of incorporating paraffin wax infused with nanomaterial beneath the COSS base. The key findings revealed significant improvements in distillate production with the COSS modifications. Compared to a standard solar still (CSS), the COSS alone demonstrated a 76 % increase in daily output. Integrating a heating coil and internal reflectors with the COSS further boosted productivity by an impressive 92 %. The most significant advancements were achieved by combining the COSS with a VWSS and additional features. The MCOSS (COSS with VWSS and internal reflectors) exhibited a remarkable 209 % increase in distillate production compared to the CSS. This value increased to a staggering 269 % when incorporating a heating coil, VWSS, and an external condenser. Adding a fan to the MCOSS further enhanced efficiency to 68 %. Notably, incorporating nanomaterial-infused paraffin wax (PCM-Ag) with the MCOSS with VWSS resulted in a 246 % increase in productivity compared to the standard design. The research also revealed a significant decrease in freshwater production costs. The cost per liter of freshwater was determined to be $0.024 for the CSS and a considerably lower $0.0126 for the MCOSS with a fan.